Pengaruh Lama Waktu Biofermentasi Chromolaena Odorata Dengan Sumber Karbon Tepung Putak Terhadap Kandungan Energi - Penuam, Rispa Ofenci Nope; Lestari, Gusti Ayu Y.; Dami Dato, Twen O (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this research is to detemine the effect of biofermentation time (Chromolaena odotara) with putak flour carbon source on energy content. The method used in this research is a complete randomized design (CRD) method consisting of 4 treatments and 4 replicates. The treatments applied were: LBf21: 21 days biofermentation time (as control), LBf14: biofermentation time, LBf7: fermentation time an/d LBf0 biofermentation time. The variable studied was the energy content (CHO, BETN, GE, ME, TDN) of white flower bush silage with carbon source of putak flour. The data obtained were analyzed using analysis of variance. The results of statistical analysis showed that the addition of putak flour as a carbon source had no significant effect (P>0.05) on energy content with different lengths of biofermentation time. It was concluded that the length of Chromolaena odorata biofermentation with putak flour carbon source did not affect the energy content.